Feasibility study on collecting patient‐reported outcomes from breast cancer patients using the LINE‐ePRO system. Issue 5 (26th March 2022) - Hayashida, Tetsu; Nagayama, Aiko; Seki, Tomoko; Takahashi, Maiko; Matsumoto, Akiko; Kubota, Anna; Jinno, Hiromitsu; Miyata, Hiroaki; Kitagawa, Yuko
Abstract: Due to the increasing complexity of cancer treatment, ensuring safety and maintaining the quality of life during treatment are important issues. Patient‐reported outcomes (PROs) in oncology are essential for assessing patient symptoms. A feasibility study was undertaken on breast cancer patients by building a PRO data collection system based on LINE, one of the most popular social network service applications in Japan. In this study, one or more predefined PRO questions for each breast cancer patient's clinical situation were sent to the patient's LINE application daily. The patient selected a predefined answer by tapping the screen, but no free‐text answers were allowed. Seventy‐three patients were enrolled. The median observation period was 435 days (84‐656 days), and the total number of PROs collected was 16, 417, with a mean of 224.9 reports per patient. Patients on adjuvant endocrine therapy were notified of 2.5 questions per week, and the median number of responses per week and response rate were 2.387 (1.687‐11.627) and 95.5%, respectively. Analyzing the results by age group, the number of responses from those aged 60 and above was equal to or higher than that of the younger age group. It was also possible to track each patient's PROs accurately. These results suggested that the design of the system, based on an application used daily, instead of using specifically prepared applications for collecting electronic PROs, was the reason for the favorable acceptance from patients and the satisfactory response rate from all age groups, including the elderly. Abstract : This study aimed to determine the feasibility of the LINE electronic patient‐reported outcome (ePRO) system to be accepted by breast cancer patients and to successfully collect ePRO data using LINE, which is the most popular social network service application in Japan. Our study suggests that the acceptance of the system by the patients was favorable, and the response rate was satisfactory. Therefore, building a PRO reporting system based on the applications frequently used by the citizens of a country is likely to contribute to improving the response rate.